Grundgesetz und Rassismus - Froese, Judith; Thym, Daniel (Mohr Siebeck, 2022)
The term »racism« is currently experiencing a renaissance in Germany. In parts of academia, a broad understanding dominates, which also covers culturalised distinctions as well as institutional manifestations that are not based on intentional actions. In this collection, leading scholars present a range of different perspectives and show which of these manifestations of racism are covered by the legal prohibitions of discrimination in the German constitution, EU law, and international law.